Evaluasi Penerapan Program Hafalan Juz 30 Pada Mahasiswa Prodi Kesehatan Masyarakat UIN Alauddin Makassar - Dian Rezki Wijaya; Zilfadhilah Arranury (At-Tarbawi: Jurnal Kajian Kependidikan Islam, 2021)
The program of tahfidz al-Quran is one of the leading programs that are in great demand by the public in many campuses. However, the reality, there are still some obstacles experienced in the implementation of the program. Therefore, this study focusses on the implementation of the Juz 30 memorization program for students of the Public Health Study Program at UIN Alauddin Makassar to find out the extent of the success rate of implementing the program. This research uses descriptive quantitative research with CIPP evaluation method (context, input, process and product) with a research sample of 121 students. The results showed that the evaluation of all CIPP indicators for the implementation of the juz 30 memorization program for students of the Public Health Study Program of UIN Alauddin Makassar were categorized as good with an average score of 3.63. however, it needs an active role from the academic advisory lecturers to always remind students to deposit memorization according to the schedule determined by the established procedure.